2014
DOI: 10.1371/journal.pone.0088644
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin Inhibits Glutamate Release and Prevents Kainic Acid-Induced Neurotoxicity in Rats

Abstract: An excessive release of glutamate is considered to be a molecular mechanism associated with several neurological diseases that causes neuronal damage. Therefore, searching for compounds that reduce glutamate neurotoxicity is necessary. In this study, the possibility that the natural flavone acacetin derived from the traditional Chinese medicine Clerodendrum inerme (L.) Gaertn is a neuroprotective agent was investigated. The effect of acacetin on endogenous glutamate release in rat hippocampal nerve terminals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Studies also suggest that a decrease in the activity of this enzyme may lead to an increase in Glu release mediated by NMDAR, resulting in an adverse effect on cellular integrity (Fig. 4) (Lin et al 2014;Volkow et al 2013). It has been demonstrated that intermittent ethanol treatment causes a decrease in the expression of the dopamine receptor type 2 (D2R) and a decrease in phosphorylation of 2B subunit of the NMDA receptor (NMDAR-2B) in the prefrontal cortex, hippocampus, NAc and only of D2R in the striatum (Pascual et al 2009).…”
Section: Changes In Glutamatergic and Dopaminergic Pathwaysmentioning
confidence: 99%
“…Studies also suggest that a decrease in the activity of this enzyme may lead to an increase in Glu release mediated by NMDAR, resulting in an adverse effect on cellular integrity (Fig. 4) (Lin et al 2014;Volkow et al 2013). It has been demonstrated that intermittent ethanol treatment causes a decrease in the expression of the dopamine receptor type 2 (D2R) and a decrease in phosphorylation of 2B subunit of the NMDA receptor (NMDAR-2B) in the prefrontal cortex, hippocampus, NAc and only of D2R in the striatum (Pascual et al 2009).…”
Section: Changes In Glutamatergic and Dopaminergic Pathwaysmentioning
confidence: 99%
“…DFT studies revealed that the high antioxidant power of the molecule could be due to the abstraction of hydrogen atoms from the ortho hydroxyl groups, characterizing both its A and B rings (Cao et al, 2005). The sample Oct12 is the only one that contained as constituent acacetin, a well known antioxidant, anti-inflammatory and anticancer natural substance, recently proposed as a therapeutic agent for the treatment of neuropsychiatric disorders (Lin et al, 2014). The evaluation of the Fe 3+ reducing power strongly correlated with the TPC values (Table 3).…”
Section: Antioxidant Activity Of Extracts T Longicaulismentioning
confidence: 99%
“…Fluoro-Jade B-positive cells in the CA3 region of hippocampus was determined as previously described. 30,31) Immunohistochemistry The sections were washed with 0.1 M PBS and blocked with 0.5% normal goat serum in 0.1 M PBS for 1 h at room temperature. Primary antibody (mouse monoclonal anti-OX-42 antibody, 1 : 1000; AbD Serotec, Oxford, U.K.) incubation was performed two overnight at 4°C.…”
Section: Glutamate Levels Determinationmentioning
confidence: 99%